Population Based Cancer Screening Programmes as a Teachable Moment for Primary Prevention Interventions. A Review of the Literature - Senore, Carlo; Giordano, Livia; Bellisario, Cristina; Di Stefano, Francesca; Segnan, Nereo (Frontiers in Oncology, 2012)
Background and aim. Unhealthy diets, physical inactivity and smoking are key risk factors for the major non-communicable diseases such as cancer, cardiovascular diseases and diabetes. The screening procedure may represent an ideal setting for promoting healthy lifestyles as they represent a time when subjects are probably more inclined to consider a relationship between their own habits and their effects on health. The aim of this study is to review available evidence concerning interventions combining screening and primary prevention interventions, aimed at promoting the adoption of healthy lifestyles. Methods. We searched the MEDLINE and Cohcrane library electronic databases for intervention studies of primary prevention interventions implemented in the context of established screening programmes, or of pilot screening projects, where the study design included a comparison group. Results. Comprehensive interventions are acceptable for asymptomatic subjects targeted for cancer screening, can result in improvements and may be cost-effective. A positive impact of these interventions in favouring the adoption of cancer protective dietary behaviours was observed in all studies. Conflicting results were instead reported with respect to physical activity, while no impact could be observed for interventions aimed to favour smoking cessation. Conclusions. The retrieved studies suggest that the screening setting may offer valuable opportunities to provide credible, potentially persuasive life style advice, reaching a wide audience. A multiple risk-factor approach may maximise the benefit of behavioural change, as the same health related habits are associated not only with cancers targeted by screening interventions, but also with other cancers, coronary artery disease and other chronic conditions, while unhealthy behaviours may be mutually reinforcing. In order to cover a maximum number of possibilities, health education programmes should include multiple strategies, inte